Samuel Daniel’s authorial strategies in The Queenes Arcadia (1606) - Christine Sukic (Etudes Epistémè)
This article focuses on Samuel Daniel’s The Queenes Arcadia, performed in 1605 as Arcadia Reformed and first published in 1606. Daniel’s use of the genre of the pastoral drama is quite telling in his construction as an author. He uses self-reflexive devices in the play, and meta-poetic intrusions within the plot, thus confirming that he saw himself as an author. I examine the different poetic styles used in the play as well as the circumstances of the first staging of the play at Oxford on the occasion of a royal visit there in order to define Daniel’s authorial strategies.